Topical Theme Depicted in the Speech of Indonesian Minister of the State Secretariat - Danang Satria Nugraha (Universitas PGRI Sumatera Barat, 2024)
The speech of Indonesian stakeholders (SIS) is ideal for not only discourse analysis but also as an instance of language employed for systemic functional linguistics (SFL). According to the SFL perspective, the use of morphosyntax and morphosemantics features in the speech of the Indonesian ministry of state secretariat is an expression of informational content that has been incorporated into the structure of language. The objective of this study was to describe the informative content in the form of a topical theme in the SIS practices conducted by the Indonesian minister of state secretariat (MSS) in 2019–2024. The data for this study consisted of transcribed utterances taken from speeches by MSS. The MSS official broadcasting platform and other relevant YouTube channels were the data providers. Documentation, transcription, and comprehensive textual fragmentation techniques were used to collect and analyze the data. This analysis demonstrates that, with relation to the SFL, practically all of the studied MSS utterances contain topical theme. The topical theme has been organized using phrases and sentences. Additionally, the topical theme has served as both a standalone theme and a component of multiple themes. This study proposal pertains to a more in-depth examination of the interrelationships between topical theme and other sorts of theme or rheme.